Identifying M&A targets and the information content of VC/PEs - Qingquan Tang; Wenfei Li (China Journal of Accounting Research, 2018)
The information gap in the M&A market hinders acquirers from effectively identifying high-quality targets. We examine whether VC/PEs convey information content in the M&A market and whether acquirers can use such information to identify high-quality targets. We show that VC/PEs have significant information content and can signal high-quality target companies via "certification". When acquirers lack acquisition experience and targets are located in inferior information environments, VC/PE "certification" is more significant. The better reputation a VC/PE has, the more information it conveys. Syndicate VC/PEs convey stronger information than independent VC/PEs. We also find that acquirers do not pay higher premiums for high-quality targets. Overall, our results suggest that VC/PEs have value relevance in the M&A market, confirming their "certification" role. We present means for acquirers to select high-quality targets and investors to build efficient portfolios.
Keywords: 650; M&A; Certification; VC/PEs; Information content